Integrated Single-Cell Transcriptome Analysis Reveals Novel Insights into the Role of Opioid Signaling in the Pathophysiology of Inflammatory Bowel Disease - Mudan Zhang; Zhuo Xie; Shenghong Zhang; Gaoshi Zhou (Biomedicines)
Background/Objectives: Inflammatory bowel disease (IBD), encompassing Crohn’s disease (CD) and ulcerative colitis (UC), is characterized by chronic gastrointestinal inflammatory diseases with complex etiology and remains a therapeutic challenge due to heterogeneous treatment responses. Opioids are widely used for analgesic management in IBD, yet the role of opioid signaling in IBD remains unclear. Methods: We employed single-cell RNA sequencing (scRNA-seq), bulk RNA sequencing, CellChat analysis, and transcription factor activity assessment to systematically investigate the roles and underlying mechanisms of opioid signaling-related genes in IBD. Results: We characterized opioid signaling-related genes in IBD at single-cell resolution and identified a novel subset of monocytes with a high expression level of opioid signaling-related genes (OpiHi monocytes). OpiHi monocytes were enriched in IBD tissues and served as a predominant source of tumor necrosis factor (TNF)-related signaling in the tissues of IBD. An inflammatory microenvironment in IBD drove the generation of OpiHi monocytes. Moreover, the prediction model based on OpiHi monocytes marker genes had robust predictive performance for the therapeutic response to anti-TNF therapy in IBD. Conclusions: This study provides novel insights into opioid signaling in IBD pathogenesis at the cellular level and establishes a reliable biomarker for precise management of anti-TNF therapy.